Trusted computing mobile terminal application research based on biometric trusted access protocol - Jun XU (网络与信息安全学报)
The architecture of safety production monitoring platform was discussed based on the discussion of the TPM trusted platform, the hardware architecture based on trusted mobile platform of ARM + DSP dual core proces-sor was proposed, the user access to the process of biometric authentication and user terminal hardware authentica-tion properties of registration protocol were proposed, and its performance was analyzed. The experimental results show that the new protocol has a small increase in the time overhead, and the fingerprint template is updated in TPM, which effectively increases the recognition rate.